Pengaruh Work Life Balance terhadap Kepuasan Kerja pada Karyawan PT PLN (Persero) Indonesia Power Unit Bisnis Pembangkitan Ombilin di Sawahlunto - Hendra, Yuda Septiadi; Dwatra, Free Dirga (ARZUSIN, 2024)
This research aims to determine and analyze the influence of work life balance on employee job satisfaction at PT. PLN Indonesia Power Ombilin Generation Business Unit in Sawahlunto. This research uses quantitative correlational methods. The population in this study were employees of PT. PLN Indonesia Power Ombilin Generation Business Unit in Sawahlunto. The sampling technique in the research used a saturated sample technique with a total of 89 respondents. The instrument in this study used the work life balance scale by Fisher et al. (2009) which was then adapted from the scale compiled by Gunawan (2019). Job satisfaction was measured using the Luthans (2006) scale which was then adapted from the scale compiled by Elvani (2019). Data was collected by distributing questionnaires online using Google forms, then the data was processed using simple linear regression analysis with the help of IBM SPSS 20. Hypothesis test results showed significant results of 0.160 > 0.05, which means there is no influence of work life balance on employee job satisfaction. PT. PLN Indonesia Power Ombilin Generation Business Unit in Sawahlunto. This means that the higher the work life balance will not affect the level of employee job satisfaction. This shows that Ha is rejected and H0 is accepted.